All Days 1991
DOI: 10.2118/22000-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Testing of an Ultra-High-Pressure, Jet-Assisted Drilling System

Abstract: Small-scale laboratory tests of an ultrahigh-pressure jet-assisted drilling system have been carried out in a pressure drilling test stand. Increases in the penetration rate are greatest in permeable rock and are proportional to the hydraulic pressure. The results of field tests with the drilling system are consistent with those obtained in the laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Water drive development is the main development of Shengli Oilfield. Digging deeper into the potential of remaining oil in water flooding reservoirs and increasing oil recovery are the foundation and key to achieving the eastern stability (Kolle et al, 1991;Vance and Kent, 2001). Shengli Oilfield water flooding reservoir integrated water 92.9%, some oil fields have risen to 96%, have entered the high water, high water-cut development period which bring great challenges to effective development (Boudaoud et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water drive development is the main development of Shengli Oilfield. Digging deeper into the potential of remaining oil in water flooding reservoirs and increasing oil recovery are the foundation and key to achieving the eastern stability (Kolle et al, 1991;Vance and Kent, 2001). Shengli Oilfield water flooding reservoir integrated water 92.9%, some oil fields have risen to 96%, have entered the high water, high water-cut development period which bring great challenges to effective development (Boudaoud et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The current technologies (Kolle et al, 1991;Vance and Kent, 2001) choose the screw pump and the screw motor to rely on the experience. The target displacement and the variable pressure amplitude are not the optimal values.…”
Section: Introductionmentioning
confidence: 99%
“…However, the slow drilling speed limits the drilling of deep/ultradeep wells. To overcome this challenge, researchers have developed a number of tools to increase drilling speed, including downhole motor device, rotary percussion drilling tools, downhole hydraulic pulsed cavitation jet generators, and downhole torsional drilling tools [6][7][8][9][10][11][12][13][14][15][16][17]. Although these tools differ in working mechanisms, their energies are all from drilling fluid.…”
Section: Introductionmentioning
confidence: 99%
“…With the exploration and development of oil and gas shifting from shallow to deep formation, the deep and ultra-deep wells drilling must confront the problems of slow drilling rate and high cost. Extensive laboratory and field studies have shown that high-pressure jets have the potential for significantly improving the rate of penetration (ROP) during the drilling of oil and gas wells [1,2]. Based on the above experimental results, the ultrahigh-pressure-jet-assisted drilling technique is developed and turned into a main method to increase the ROP in the drilling of deeper gas and oil wells where the rocks become harder and more difficult to drill.…”
Section: Introductionmentioning
confidence: 99%